Solid Lipid Nanoparticles Containing Morin: Preparation, Characterization, and Ex Vivo Permeation Studies - Federica De Gaetano; Consuelo Celesti; Giuseppe Paladini; Valentina Venuti; Maria Chiara Cristiano; Donatella Paolino; Daniela Iannazzo; Vincenza Strano; Anna M. Gueli; Silvana Tommasini; Cinzia Anna Ventura; Rosanna Stancanelli (MDPI AG, 2023)
In recent years, bioactive compounds have been the focus of much interest in scientific research, due to their low toxicity and extraordinary properties. However, they possess poor solubility, low chemical stability, and unsustainable bioavailability. New drug delivery systems, and among them solid lipid nanoparticles (SLNs), could minimize these drawbacks. In this work, morin (MRN)-loaded SLNs (MRN-SLNs) were prepared using a solvent emulsification/diffusion method, using two different lipids, Compritol® 888 ATO (COM) or Phospholipon® 80H (PHO). SLNs were investigated for their physical-chemical, morphological, and technological (encapsulation parameters and in vitro release) properties. We obtained spherical and non-aggregated nanoparticles with hydrodynamic radii ranging from 60 to 70 nm and negative zeta potentials (about −30 mV and −22 mV for MRN-SLNs-COM and MRN-SLNs-PHO, respectively). The interaction of MRN with the lipids was demonstrated via μ-Raman spectroscopy, X-ray diffraction, and DSC analysis. High encapsulation efficiency was obtained for all formulations (about 99%, w/w), particularly for the SLNs prepared starting from a 10% (w/w) theoretical MRN amount. In vitro release studies showed that about 60% of MRN was released within 24 h and there was a subsequent sustained release within 10 days. Finally, ex vivo permeation studies with excised bovine nasal mucosa demonstrated the ability of SLNs to act as a penetration enhancer for MRN due to the intimate contact and interaction of the carrier with the mucosa.